Nuclear Progestin Receptor (Pgr) Knockouts in Zebrafish Demonstrate Role for Pgr in Ovulation but Not in Rapid Non-Genomic Steroid Mediated Meiosis Resumption - Zhu, Yong; Liu, Dongteng; Shaner, Zoe C.; Chen, Shixi; Hong, Wanshu; Stellwag, Edmund J. (Frontiers in Endocrinology, 2015)
Progestins, progesterone derivatives, are the most critical signaling steroid for initiating final oocyte maturation (FOM) and ovulation, in order to advance fully-grown immature oocytes to become fertilizable eggs in basal vertebrates. It is well-established that progestin induces FOM via an elusive membrane receptor and a nongenomic steroid signaling process, which precedes progestin triggered ovulation that is mediated through a nuclear progestin receptor (Pgr) and genomic signaling pathway. To determine whether Pgr plays a role in a nongenomic signaling mechanism during FOM, we knocked out Pgr in zebrafish using transcription activator-like effector nucleases (TALENs) and studied the oocyte maturation phenotypes of Pgr knockouts (Pgr-KOs). Three TALENs-induced mutant lines with different frame shift mutations were generated. Homozygous Pgr-KO female fish were all infertile while no fertility effects were evident in homozygous Pgr-KO males. Oocytes developed and underwent FOM normally in vivo in homozygous Pgr-KO female compared to the wildtype controls, but these mature oocytes were trapped within the follicular cells and failed to ovulate from the ovaries. These oocytes also underwent normal germinal vesicle breakdown (GVBD) and FOM in vitro, but failed to ovulate even after treatment with human chronic gonadotropin (HCG) or progestin (17alpha,20beta-dihydroxyprogesterone or DHP), which typically induce FOM and ovulation in wildtype oocytes. The results indicate that anovulation and infertility in homozygous Pgr-KO female fish was, at least in part, due to a lack of functional Pgr-mediated genomic progestin signaling in the follicular cells adjacent to the oocytes. Our study of Pgr-KO supports previous results that demonstrate a role for Pgr in steroid-dependent genomic signaling pathways leading to ovulation, and the first convincing evidence that Pgr is not essential for initiating nongenomic progestin signaling and triggering meiosis resumption.